Dynamics of Remittances and Economic Development in Nigeria - Ayewumi Ezonfade Fredrick; Anastasia Chi-chi Onuorah; Casmir Chinemerem Osuji (CV. Proaksara Global Transeduka, 2025)
This study adopts a bird’s-eye perspective to examine the dynamics of remittances within the Nigerian migration context. Drawing on multiple theoretical frameworks, it explores the relationship between remittance inflows and economic development using secondary data from the Central Bank of Nigeria and the National Bureau of Statistics for the period 1994–2023. Key variables include workers’ remittances per capita, gross capital formation, consumer price index, foreign direct investment, exchange rate, and the human capital development index. Using an error correction mechanism, the study finds a significant positive relationship between remittance inflows and human capital development, suggesting that a 1% increase in remittances may lead to a 44.9% rise in economic development. However, remittances from foreign direct investment (t = 0.741, p = 0.477), gross capital formation (t = 0.598, p = 0.564), and consumer price index (t = 0.214, p = 0.836) show no statistically significant effect on economic development. The study recommends that remittance-receiving countries like Nigeria implement robust macroeconomic policies such as stable exchange rates, improved infrastructure, and market integration to create an enabling environment for sustained growth. By offering empirical insights into how various remittance-related factors impact economic development, this study contributes to the literature and addresses a notable research gap in the Nigerian context.